Consolidating Russia and Eurasia Antibiotic Resistance Data for 1992–2014 Using Search Engine - Bedenkov, Alexander; Shpinev, Vitaly; Suvorov, Nikolay; Sokolov, Evgeny; Riabenko, Evgeniy (Frontiers in Microbiology, 2016)
Background: The World Health Organization recognizes the antibiotic resistance problem as a major health threat in the 21st century. The paper describes an effort to fight it undertaken at the verge of two industries - healthcare and Data Science. One of the major difficulties in monitoring antibiotic resistance is low availability of comprehensive research data. Our aim is to develop a nation-wide antibiotic resistance database using Internet search and data processing algorithms using Russian language publications. Materials and methods: An interdisciplinary team built an intelligent Internet search filter to locate all publicly available research data on antibiotic resistance in Russia and Eurasia countries, extracted it, and collated it for analysis. A database was constructed using data from 850 original studies conducted at 153 locations in 12 countries between 1992 and 2014. The studies contained susceptibility and resistance rates of 156 microorganisms to 157 antibiotic drugs. Results: The applied search methodology was highly robust in that it yielded search precision of 58% versus 20% in a typical Internet search. It allowed finding and collating within the database the following data items (among many others): publication details including title, source, date, authors, etc.; study details: time period, locations, research organization, therapy area, etc.; microorganisms and antibiotic drugs included in the study along with prevalence values of resistant and susceptible strains, and numbers of isolates. The next stage in project development will try to validate the data by matching it to major benchmark studies; in addition, a panel of experts will be convened to evaluate the outcomes. Conclusions: The work provides a supplementary tool to national surveillance systems in antibiotic resistance, and consolidates fragmented research data available for 12 countries for a period of more than 20 years.